Geotechnical Properties of Soil-Lightweight Aggregate Mixtures - Aljboori, Wurood; Al-Soud, Madhat Shakir; Ali, Asma Mahdi (Engineering, Technology & Applied Science Research, 2025)
This study investigates the stabilization and strengthening of clayey soils using several Lightweight Aggregates (LWAs), including Lightweight Expanded Clay Aggregate (LECA), Ponza (Pumice), and Thermostone. LWAs were incorporated into the soil to evaluate their impact on critical geotechnical parameters, such as compaction, consolidation, Unconfined Compressive Strength (UCS), and shear strength. The results revealed that incorporating LWAs effectively reduces the soil density, increases the void ratios, and enhances certain soil properties. LECA demonstrated the most substantial impact in decreasing soil density and increasing porosity, achieving a maximum density reduction of 60% and a void ratio increase of 75% at a 60% addition. While LWAs enhanced the internal friction angle by up to 90% -with Thermostone showing the highest increase at a 60% addition- cohesion diminished across all concentrations. The UCS peaked with a 94% increase at a 10% LECA addition but decreased with higher LWA percentages due to the porous nature of the additives disrupting the soil matrix. Optimal performance was observed with LWA concentrations between 10% and 30%, balancing improved strength and soil integrity. These findings suggest that LWAs can effectively stabilize and strengthen clayey soils, particularly in applications requiring reduced weight and enhanced shear strength, provided that the mixing ratios are carefully calibrated to align with project-specific requirements.